Racial disparities in low‐value surgical care and time to surgery in high‐volume hospitals. Issue 2 (1st December 2020) - Jackson, Destiny K.; Li, Yaming; Eskander, Mariam F.; Tsung, Allan; Oppong, Bridget A.; Bhattacharyya, Oindrila; Paskett, Electra D.; Obeng‐Gyasi, Samilia
Abstract: Background: The objective of this study is to examine racial differences in receipt of low‐value surgical care and time to surgery (TTS) among women receiving treatment at high‐volume hospitals. Methods: Stage I–III non‐Hispanic Black (NHB) and Non‐Hispanic White (NHW) breast cancer patients were identified in the National Cancer Database. Low‐value care included (1) sentinel lymph node biopsy (SLNB) among T1N0 patients age ≥70 with hormone receptor–positive cancers, (2) axillary lymph node dissection (ALND) in patients meeting ACOSOG Z0011 criteria, and (3) contralateral prophylactic mastectomy (CPM) with unilateral cancer. TTS was days from biopsy to surgery. Bivariate and logistic regression analyses were used to compare the groups. Results: Compared to NHWs, NHBs had lower rates of SLNB among women age ≥70 with small hormone–positive cancers (NHB 58.5% vs. NHW 62.2% p  < .001) and CPM (NHB 26.3% vs. NHW 36%; p  < .001). ALND rates for patients meeting ACOSOG Z0011 criteria were similar between both groups ( p  = .13). The odds of surgery >60 days were higher among NHBs (odds ratio, 1.77; 95% confidence interval, 1.64–1.91; NHW ref). Conclusions: NHBs treated at high‐volume hospitals have higher rates of surgical delay but are less likely to undergo low‐value surgical procedures compared to NHW women.